Zinc transporters ZnT3 and ZnT6 are downregulated in the spinal cords of patients with sporadic amyotrophic lateral sclerosis. Issue 2 (3rd October 2014) - Kaneko, Masayuki; Noguchi, Takao; Ikegami, Saori; Sakurai, Takeyuki; Kakita, Akiyoshi; Toyoshima, Yasuko; Kambe, Taiho; Yamada, Mitsunori; Inden, Masatoshi; Hara, Hideaki; Oyanagi, Kiyomitsu; Inuzuka, Takashi; et al.
<x xml:space="preserve">Abstract</x> The loss of homeostasis of essential metals is associated with various diseases, including neurodegenerative diseases. Previous studies have shown that the levels of zinc (Zn) are significantly higher in the cerebrospinal fluid of patients with amyotrophic lateral sclerosis (ALS). Zn transporters and metallothioneins tightly control intracellular and extracellular Zn levels. This study investigated the protein levels of ZnT, a Zn transporter family, in ALS patients and model mice. The mRNA expression of ZnT1, −3, −4, −5, −6, −7, and −10 was assessed in the spinal cords of human control subjects. ZnT3 and ZnT6 protein levels were significantly diminished in the spinal cords of sporadic ALS patients compared with controls. Furthermore, immunohistochemical staining demonstrated decreased ZnT3 and ZnT6 immunoreactivity in the ventral horn of the spinal cords in ALS patients. Moreover, immunohistochemical analysis revealed that all ZnTs expressed in the spinal cords were localized in a distinct subset of motor neurons. In addition, ZnT3 and ZnT6 protein levels were not altered in SOD1 (G93A) mutant transgenic mice before or after the onset of ALS symptoms compared with controls. These results suggest that ZnT3 and ZnT6 protein levels are decreased in the spinal cords of sporadic ALS patients; however, this did not occur merely via loss of motor neurons. © 2014 Wiley Periodicals, Inc.